The words of prevention, part II: ten terms in the realm of quaternary prevention - Marc Jamoulle; Enrique Gavilán; Raquel Vaz Cardoso; María Ana Mariño; Miguel Pizzanelli; Julien Grosjean; Stéfan J. Darmoni (Sociedade Brasileira de Medicina de Família e Comunidade, 2015)
Objective: This part II article about the 'words of prevention' presents in a terminological way the content of ten current concepts used in the prevention domain which are closely linked to quaternary prevention: (1) overinformation, (2) overdiagnosis, (3) medically unexplained symptoms, (4) overmedicalisation, (5) incidentaloma, (6) overscreening, (7) overtreatment,  (8) shared decision making, (9) deprescribing, and (10) disease mongering. Methods: with the support of the laboratory team of the University of Rouen, France, which is dedicated to medical terminology and semantic relationships, it was possible to utilize  a graphic user interface (called DBGUI) allowing the construction of links for each of chosen terms, and making automatic links to MeSH, if any. Those concepts are analyzed in their environment in current literature, as well as in their MeSH counterparts, if any, and related semantic online terminologies. Results and Discussion: The rules in terminological development aspire to cover the whole field of a concept and in the meantime, it helps to avoid the noise due to proxy and not exactly related issues. This refers to exhaustivity and specificity in information retrieval. Our finds show that referring to MeSH only in information retrieval in General Practice/Family medicine can induce much noise and poor adequacy to the subject investigated. Conclusion: Gathering concepts in specially prepared terminologies for further development of ontologies is a necessity to enter in the semantic web area and the era of distributed data.